Trade Secrets at the International Trade Commission: A Survey - Riley, Andrew; Stroud, Jonathan (Science and Technology Law Review, 2013)
Companies clamoring for looser trade restrictions, expanded overseas market access, and advances in technology have achieved stunning successes in the last decade, but that internationalism has come at a price. Building factories, researching, developing, and manufacturing products, processes, and computer systems in our globally connected world creates daunting challenges when a company suddenly faces the theft of intellectual property. Compounding this, uneven international enforcement of intellectual property—particularly economic espionage and the theft of trade secrets—strains companies seeking to protect innovative investments. Worse still, the bad actor is often extra-national, and the pilfered goods can be information or relatively abstract yet nonetheless valuable goods. Because of recent developments in U.S. long-arm jurisdiction and a legal presumption against the extraterritorial application of domestic laws, plaintiffs in U.S. courts often fail to achieve results, and often meet unresponsive defendants with little at stake. Enter the U.S. International Trade Commission. In the wake of TianRui Group Co. v. ITC, savvy companies have sought to use this unique forum to protect their domestic U.S. market and achieve unique discovery goals, and, at the least, enter international disputes with the bargaining chip of threatened litigation backed up by a powerful remedy and broad jurisdiction. The follow-on investigations of Certain Rubber Resins and Processes for Manufacturing Same, Certain Robotic Toys and Components Thereof, and Certain Paper Shredders, Certain Process for Manufacturing or Related to Same, all demonstrate the value such actions provide. This resurgence is justified. This paper seeks to explain in detail this tool useful against white-collar theft—§ 337 trade secret actions. Almost thirty years ago, Congress empowered the ITC, through trial-like investigations on a truncated timeline, to exclude goods entirely from the U.S. Although growing in recent years, this little-known means of enforcement has distinct advantages over traditional litigation. In rem jurisdiction, powerful remedies, and a shortened timeline often concludes with better results for parties confronted with difficult situations. Importantly, the ITC’s doors are open to both foreign-originating and U.S.-based parties as long as the parties can establish the jurisdictional requirements. While the scholar Colleen Chien empirically analyzed most of the patent actions brought at the ITC, no survey of the trade secret complaints filed with the ITC yet exists—so the authors created one. In so doing, we demonstrate that these actions are an intensive, complicated, and exciting means of investment protection that has developed into a potent option for the corporate victims of bad actors and economic espionage.